STUDI PEMETAAN DATA BASE SPASIAL PENGGUNAAN LAHAN BERBASIS SISTEM INFORMASI GEOGRAFIS DI KELURAHAN BAURUNG - Muhammad Harum Muhammad Harum (Universitas Sulawesi Barat, 2020)
ABSTRACT: Geographic Information Systems not only handle maps or images, but most importantly is the ability to handle large volumes of databases. The database concept is the center of a Geographic Information System and is a simple system that can only produce output in the form of geographical and spatial data from a region. The Geographical Information System Database (GIS) is formed having a spatial data topology structure, and can be used as basic data. The database is formed automatically from the results of surveys and measurements and the results of digitization of high-resolution image maps so that spatial data information can be obtained, to produce a new Geographic Information System database as a result of the merging of survey data and the results of digitization of image maps.